2018
DOI: 10.1088/2399-6528/aab7e5
|View full text |Cite
|
Sign up to set email alerts
|

Zero modes of the Kitaev chain with phase-gradients and longer range couplings

Abstract: We present an analytical solution for the full spectrum of Kitaevʼs one-dimensional p-wave superconductor with arbitrary hopping, pairing amplitude and chemical potential in the case of an open chain. We also discuss the structure of the zero-modes in the presence of both phase gradients and next nearest neighbor hopping and pairing terms. As observed by Sticlet et al, one feature of such models is that in a part of the phase diagram, zero-modes are present at one end of the system, while there are none on the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…We explore the superposition and vanishing of TQCLs through the study of Berry connection and ground-state energy. We study and analyze the ground-state energy to explain the stability of higher order WNs [21,[33][34][35]. We study the parameter space through pseudospin vectors and also derive quite a few exact solutions for the WN.…”
Section: Topological Characterization In Momentum Space and Topological Quantum Criticalitymentioning
confidence: 99%
“…We explore the superposition and vanishing of TQCLs through the study of Berry connection and ground-state energy. We study and analyze the ground-state energy to explain the stability of higher order WNs [21,[33][34][35]. We study the parameter space through pseudospin vectors and also derive quite a few exact solutions for the WN.…”
Section: Topological Characterization In Momentum Space and Topological Quantum Criticalitymentioning
confidence: 99%
“…Driven by the demand of applications, researchers devoted great effort to the stability of the topological phase in the Kitaev chain with nearest-neighboring repulsive interactions [28][29][30]. Along this line, theoretical studies also extended to issues of dimerization [31], disorder [32][33][34][35][36][37], quasi-periodicity [35,38], long-range interactions [39][40][41], quartic interactions [42], and so on. For the interacting model without disorders [43][44][45][46], both numerical and perturbative investigations showed that MZMs can be stably present with moderate interactions [43][44][45][47][48][49], which was also found to generally broaden * Electronic address: yaoyao2016@scut.edu.cn the window of chemical potential where the system is in the nontrivial topological superconducting (TSC) phase [43-45, 47, 48].…”
Section: Introductionmentioning
confidence: 99%
“…While solutions for first-order topological boundary states have been derived in several specific models [34][35][36][37][38][39][40][41][42][43][44] and several general approaches have been developed to retrieve them [45][46][47][48], there is a surprising lack of methods to find analytical solutions for these boundary wave functions that are straightforward and transparent and can be used to describe modes of any codimension. Such a method is not only of theoretical relevance but also provides practical insight on how to engineer lattices that support these states.…”
Section: Introductionmentioning
confidence: 99%